Kajian Efektifitas Penggunaan Sistem Informasi Administrasi Kependudukan Menggunakan Model Delone dan Maclean - Silvianty Ariza (LPPM Universitas Bina Sarana Informatika, 2020)
The effectiveness of the information system is the way how the Organization should develop information technology system direct behaviour when interacting with systems of information technology to help its objectives effectively and efficiently Based on the model of DeLone and McLean’s approachjjj to information system success can be represented based on the quality of the system (system quality), quality of output from the system information (information quality), quality of service system itself (service quality), user interest in using the system (intention to use), user response to information systems (user satisfaction), and the benefits obtained by companies from the information system (net benefit). To see the relationship between variable that exist in DeLone and McLean model approach will be tested by using Structural Equation Modelling (SEM).